2006
DOI: 10.1007/bf03175021
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heterotrophic aerobic marine bacteria in sediment in Eastern Harbour of Alexandria

Abstract: In Eastern Harbour (EH) of Alexandria (Egypt), where an under-water museum is planned to be built, the distribution of some heterotrophic bacteria and their relationships to physical parameters and biochemical composition of the sedimentary organic matter were investigated. The Eastern Harbour is a relatively shallow semi-closed basin and is sheltered from the sea by an artificial breakwater leaving two openings, El-Boughaz and El-Silsila. Seven stations covering the area of the EH were selected and surface se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
0
0
2
Order By: Relevance
“…The results of amino acids in the investigated area is comparable with total amino acids of the Eastern Harbor that is varied widely between 1021 µg/g in winter and 11843 µg/g in spring (Gouda et al, 2006).…”
Section: Amino Acids In Sedimentssupporting
confidence: 71%
“…The results of amino acids in the investigated area is comparable with total amino acids of the Eastern Harbor that is varied widely between 1021 µg/g in winter and 11843 µg/g in spring (Gouda et al, 2006).…”
Section: Amino Acids In Sedimentssupporting
confidence: 71%
“…Considerando a escala micrométrica relevante à célula individual, na análise de comunidades bacterianas é mais adequado que as bactérias, como a infauna maior, seja medida por volume e não por massa de sedimento (Deming & Carpenter 2008). Apesar disso, muitos autores dimensionam parâmetros bacterianos por massa de sedimento (ZoBell & Morita 1959, Deming & Colwell 1982, Rowe & Deming 1985, Wit et al 1997, Danovaro et al 1998, Danovaro & Serresi 2000, Dixon & Turley 2000, Danovaro et al 2002a,b, Luna et al 2002, Lunau et al 2005, Gouda et al 2006, Raghukumar et al 2006. A análise deste parâmetro por massa de sedimento seco origina resultados com distribuição bacteriana variando amplamente de acordo com a profundidade de coleta.…”
Section: Unidades Utilizadas Para Expressar Os Resultadosunclassified
“…Para análise de abundância utilizando-se métodos de cultivo a amostra de sedimento coletada deve ser processada logo após a coleta, no entanto pode-se realizar a preservação por curtos períodos de tempo, refrigerando-se a amostra (Gouda et al 2006). No processo de preservação das amostras para posterior determinação da abundância através da análise direta (por microscopia ou citometria em fluxo), o formol tem sido a substância mais utilizada (Jannasch & Jones 1959, Meyer-Reil et al 1978, Deming & Colwell 1982, 1985, Rowe & Deming 1985, Velji & Albright 1986a,b, Bott & Kaplan 1990, Parkes et al 1994, Epstein & Rossel 1995, Relexans et al 1996, Wit et al 1997, Danovaro et al 1998, 2002a, Schmidt et al 1998, Manini et al 2004, Duhamel & Jacquet 2006, Raghukumar et al 2006, Deming & Carpenter 2008.…”
Section: Preservação Das Amostras Para Análise De Abundância Bacterianaunclassified
“…In laundry detergents, alkaline proteases have a specialized catalytic function in the hydrolysis of protein stains like blood, milk, human perspiration, etc. The protease is now used more frequently as a detergent ingredient since it can clean effectively in non-phosphate, environmentally friendly detergents (Mei and Jiang, 2005;Gouda, 2006). An earlier investigation into the substrate preferences of E. album protease revealed that casein and haemoglobin were the two substrates for which the enzyme had the highest affinity (Chellappan et al, 2011).…”
Section: Wash Performance Studiesmentioning
confidence: 99%